“Methodology for the multichannel recording of upper limb muscle activity “ - Ovalle, Christian (2022)
“In the study of the functioning of the muscle, the study standard is to be able to analyze its behavior or functioning, this behavior is represented by a continuous signal where the muscle signal can be recorded and visualized, to perform this registration a designed circuit is required For the capture of electromyography signals, there are many options of these circuits in the market, depending on the application, the part of the body that is required to be analyzed, the best option can be chosen, in this work, we present a methodology for recording in Simultaneous 8 signals, for the characteristic use of the arm muscles, due to its special shape, which allows it to be placed in the form of a bracelet, the signals that are acquired simultaneously and individually, can be used in many applications depending on the problem and challenge, recommending for use on the arm and providing a clean signal allowing Being used in the design of detection mechanisms for some pathologies related to the arm muscles and in the design of control mechanisms for the design of prostheses. “